2017
DOI: 10.1103/physrevlett.119.163201
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of Optomechanical Strain in a Cold Atomic Cloud

Abstract: We report the observation of optomechanical strain applied to thermal and quantum degenerate 87 Rb atomic clouds when illuminated by an intense, far detuned homogeneous laser beam. In this regime the atomic cloud acts as a lens which focuses the laser beam. As a backaction, the atoms experience a force opposite to the beam deflection, which depends on the atomic cloud density profile. We experimentally demonstrate the basic features of this force, distinguishing it from the well-established scattering and dipo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…After this sort of backwards-propagating wave has passed a section, this section is not susceptible to the polarization vector of the field anymore, but it is still reactive to the gradient of the radiation force. There are some studies which have experimentally observed similar results, as the one presented in [21].…”
Section: Pump Field Parallel To Ellipsoid's Major Axissupporting
confidence: 63%
“…After this sort of backwards-propagating wave has passed a section, this section is not susceptible to the polarization vector of the field anymore, but it is still reactive to the gradient of the radiation force. There are some studies which have experimentally observed similar results, as the one presented in [21].…”
Section: Pump Field Parallel To Ellipsoid's Major Axissupporting
confidence: 63%
“…The microscopic and mean-field approaches have been shown to provide equivalent results on the presence of polaritonic modes in these clouds [13,14]. Optical forces [15,16] have also drawn some attention recently, yet the role of dipoledipole correlations have been discussed to be minor [17]. Recently, the microscopic theory emerged as an important tool to study the deviations from mean-field theory due to strong particle-particle correlations, as they appear in the high density regime [18,19] or close to the atomic resonance [20].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond single-particle physics, multiple scattering of light plays an important role in modifying these forces. For instance, the radiation pressure force is at the origin of an increase of the size of magneto-optical traps [3] whereas dipole forces can lead to optomechanical self-structuring in a cold atomic gas [4] or to optomechanical strain [5].…”
Section: Introductionmentioning
confidence: 99%